Crowdfunding and wine business: Some insights from Fundovino experience - Angela Carla Mariani; Azzurra Annunziata; Maria Carmela Aprile; Francesco Nacchia (Wine Economics and Policy, 2017)
This paper aims to achieve a deeper understanding of the opportunities offered by crowdfunding in the wine sector and offer some guidelines to entrepreneurs for running a successful campaign. For this purpose, a case study research that explores the experience of the first wine-dedicated crowdfunding platform, namely Fundovino, has been conducted. Multiple data sources were used, among which documents and archival data from the Fundovino website, an email interview to its management team and an on line questionnaire sent to a sample of projects' funders. The results suggest that crowdfunding is ideally suited for the wine sector and that winemakers could exploit both the financial and marketing opportunities offered. According to our survey, the main motivations for funding projects are the willingness to support and interact with small winemakers and the fun of being involved first-hand. So, the creation of other wine-dedicated crowdfunding platforms may help raise awareness about crowdfunding and attract funders interested in projects related to the world of wine. Running a successful crowdfunding campaign requires a significant investment of time and the development of some specific skills by proponents. Indeed, these latter should also be supported by platforms and other actors through the provision of appropriate services.
Keywords: 330; Crowdfunding platform; Financing instrument; Wine